PERANCANGAN STRATEGI DENGAN PENDEKATAN MULTI CRITERIA DECISION MAKING DALAM RANGKA PENGEMBANGAN KAMPUNG UKM TAS DI GADUKAN SURABAYA - Astria Hindratmo (Media Mahardhika, 2019)
The role of SMEs in Indonesia in the country's economy is very important. Because the development of SMEs in Indonesia is quite rapid where almost one million per year. However, many problems in the development of SMEs have even led to bankruptcy. This research has the aim of obtaining an appropriate strategy to develop SMEs especially for SMEs which are included in the superior SMEs villages such as the SMEs bag in Gadukan Surabaya. Hopefully in the future the strategy can be implemented for other SMEs in the city of Surabaya. The method used in this study is using the Delphi method for identification of factors, factor evaluation using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE), designing alternative strategies with SWOT analysis, positioning SMEs with a grand strategy matrix, and selecting strategies that right with the Analytical Hierarchy Process (AHP) method. The results obtained in this study are getting 5 strength factors, 7 weakness factors, 6 opportunity factors, and 5 threat factors. Produce 18 alternative strategies resulting from the SWOT analysis. The position of SMEs in the Grand Strategy matrix quadrant is in Quadrant I. The results of the prioritized strategy determination by the AHP method, namely the SMEs bag strategy need to collaborate with the Tourism Office to make the village Gadukan a tourist shopping place for tourists who come to Surabaya.